Investigation of the process of vibration processing of AlSi10Mg aluminum alloy samples obtained by SLS technology - E. P. Zlobin; A. I. Khaimovich; A. V. Balyakin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The results of the experiment aimed at studying the effect of vibration treatment on samples of various sizes made of AlSi10Mg alloy obtained by selective laser melting are presented. During the investigation, changes in the roughness and rounding of sharp edges are monitored depending on the size of the samples and the angle of inclination of the wall. Also, the formation of low contact zones and untreated zones during processing is studied. As a result of the experiment, a minimum surface roughness of Ra 1,2 microns is achieved. The length of the untreated zones, depending on the geometry, ranged from 0,5 mm to 6 mm. Rounding occurred most effectively in the first 4 hours of processing on the edges formed by an obtuse angle. The results obtained allow us to better understand the features of vibration processing of aluminum alloy products and optimize the process to achieve the required surface characteristics. Thus, the results of the study can be useful for various industrial sectors where aluminum alloys are used, and contribute to the further development of processing technologies for products obtained using SLM technology.